Understanding the electrochemical features of ZnFe2O4, anode for LIBs, by deepening its physico-chemical properties. (April 2023) - Spada, Daniele; Ambrosetti, Marco; Mozzati, Maria Cristina; Albini, Benedetta; Galinetto, Pietro; Cini, Alberto; Fittipaldi, Maria; Bini, Marcella
Highlights: Two ZnFe2O4 samples were prepared by co-precipitation and template syntheses. A combination of spectroscopic techniques was used to verify the sample purity. In situ synchrotron X-ray diffraction patterns were interpreted on the base of physico-chemical features. Abstract: ZnFe2 O4 (ZFO) has emerged as anode material for lithium ion batteries (LIBs) thanks to its intercalation mechanism combining conversion and alloying reactions. The understanding of electrochemical behaviour is related to the knowledge of the physico-chemical properties of electrode materials. In this paper, ZFO was prepared by co-precipitation and template syntheses, obtaining samples with different morphologies and crystallite sizes. The sample purity was verified by combining X-ray powder diffraction with spectroscopic techniques such as Micro-Raman, EPR and Mössbauer. The electrochemical features, measured by using conventional cyclic voltammetry, impedance spectroscopy, charge-discharge measurements and in situ X-ray diffraction experiments, were then interpreted on the basis of the physico-chemical features. The higher electrode area of the template ZFO, with smaller particles, is responsible for better reactivity in the first cycles, but, in the long term, a lower crystallinity of active material, leading to nano-crystalline reaction products, could determine a better reversibility. Graphical abstract: Image, graphical abstract